The Influence of The Environment And Mother’s Behaviour Towards Toddlers’ Diarrhea in Banjarbaru, South Kalimantan - Nopy Faisal; Endang Sriwahyuni; Aminudin Afandhi (Graduate Program, 2016)
Diarrhea is a disease that causes high fatality in toddlers all over the world. 1.5 million children die each year due to suffering from diarrhea. Diarrhea is still a major health problem in Banjarbaru, it is included in the top 10 diseaseas in every year. Bad water quality, bad sanitation facility and mother’s unhygienic behaviour are the major cause of diarrhea in toddlers. This research aims to analyze the influence of the environment quality and mother’s behaviour towards toddlers’ diarrhea in Banjarbaru. The research variable consists of the well quality, family latrines, wastewater disposal facility, bacteriological quality of the well water, mother’s clean and healthy living behaviours (PHBS or Perilaku Hidup Bersih dan Sehat) as well as the incidence of diarrhea in toddlers. It is conducted in Landasan Ulin Public Health Center and North Banjarbaru Public Health Center with total sample of 50 toddlers. The data analysis used is univariate, bivariate and multivariate. The results showed that the mother’s PHBS (p = 0.005; OR = 13,077) and the bacteriological quality of the well water (p = 0,041; OR = 6,966) became the most influential variables of this toddlers’ diarrhea. The activities that are required in order to control the diarrheal diseases in Banjarbaru are change the mothers’ behaviour in the prevention of toddlers’ diarrhea, improve the environment quality with Community Lead Total Sanitation Program (STBM or Sanitasi Total Berbasis Masyarakat), making a Local Regulation for wastewater management, an enhancement of officers for prevention and control of diarrhea and awarding donations for low-income citizens.Key words: diarrhea, mother’s behaviour, sanitation, water,